(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we study carbon emission trading whose market is gaining popularity as a policy instrument for global climate change. The mathematical model is presented for pricing options on CO_2 emission allowance futures with jump diffusion processes, and a so-called fitted finite volume method is proposed to solve the pricing model for the spatial discretization, in which the Crank-Nicolson is employed for time stepping. In addition, the stability and the convergence of the fully discrete scheme are given, and some numerical results, which are compared with the closed form solution and the Monte Carlo simulation solution, are provided to demonstrate the rates of convergence and the robustness of the numerical method.